Viral Induced Effects on a Vulnerable Epithelium; Lessons Learned From Paediatric Asthma and Eosinophilic Oesophagitis - Watkinson, Rebecca L.; Looi, Kevin; Laing, Ingrid A.; Cianferoni, Antonella; Kicic, Anthony (Frontiers in Immunology, 2021)
The epithelium is integral to the protection of many different biological systems and for the maintenance of biochemical homeostasis. Emerging evidence suggests that particular children have epithelial vulnerabilities leading to dysregulated barrier function and integrity, that resultantly contributes to disease pathogenesis. These epithelial vulnerabilities likely develop in utero or in early life due to various genetic, epigenetic and environmental factors. Although various epithelia are uniquely structured with specific function, prevalent allergic-type epithelial diseases in children potentially have common or parallel disease processes. These include inflammation and immune response dysregulation stemming from atypical epithelial barrier function and integrity. Two diseases where aetiology and pathogenesis are potentially linked to epithelial vulnerabilities include Paediatric Asthma and Eosinophilic Oesophagitis (EoE). For example, rhinovirus C (RV-C) is a known risk factor for paediatric asthma development and is known to disrupt respiratory epithelial barrier function causing acute inflammation. In addition, EoE, a prevalent atopic condition of the oesophageal epithelium, is characterised by similar innate immune and epithelial responses to viral injury. This review examines the current literature and identify the gaps in the field defining viral-induced effects on a vulnerable respiratory epithelium and resulting chronic inflammation drawing from knowledge generated in acute wheezing illness, paediatric asthma and EoE. Besides highlighting the importance of epithelial structure and barrier function in allergic disease pathogenesis regardless of specific epithelial sub-types, this review identifies the importance to examine other parallel allergic-type disease processes that may uncover commonalities driving disease pathogenesis. This in turn may be helpful to develop common therapeutics for current clinical management and in the future disease prevention.